Buddhisme og Singhalesisk folkereligion - Andersen, Jørgen Østergaard (Religionsvidenskabeligt Tidsskrift, 1985)
The symbolic relationship between the monk (bikkhu) and the lay Singhalese (dāyaka) is analysed and discussed as complementary ways of perceiving the image of Buddha and the Truth taught by Buddha. Buddhist philosophy concerning ‘time’, ‘being’ and ‘causality’ is discussed in order to analyse the complementary relationship between ‘truth’ and ‘illusion’ and between ‘wisdom’ and ‘belief’ which are seen as ways of expressing the relationship between Theravada-Buddhism and popular Singhalese Buddhism. Jacques Lacan’s distinction between ‘l’œil’ and ‘regard’ is introduced in order to fertilize the discussion of the way monks are structuring the conceptual space, which is thought to be a substantial reality by the lay Singhalese.